Role of expression site switching in the development of resistance to human Trypanosome Lytic Factor-1 in Trypanosoma brucei brucei - Kieft, Rudo (Elsevier/North-Holland Biomedical Press, 2012)
Human high-density lipoproteins (HDLs) play an important role in human innate immunity to infection by African trypanosomes with a minor subclass, Trypanosome Lytic Factor-1 (TLF-1), displaying highly selective cytotoxicity to the veterinary pathogen Trypanosoma brucei brucei but not against the human sleeping sickness pathogens Trypanosoma brucei gambiense or Trypanosoma brucei rhodesiense. T. b. rhodesiense has evolved the serum resistance associated protein (SRA) that binds and confers resistance to TLF-1 while T. b. gambiense lacks the gene for SRA indicating that these parasites have diverse mechanisms of resistance to TLF-1. Recently, we have shown that T. b. gambiense (group 1) resistance to TLF-1 correlated with the loss of the haptoglobin/hemoglobin receptor (HpHbR) expression, the protein responsible for high affinity binding and uptake of TLF-1. In the course of these studies we also examined TLF-1 resistant T. b. brucei cell lines, generated by long-term in vitro selection. We found that changes in TLF-1 susceptibility in T. b. brucei correlated with changes in variant surface glycoprotein (VSG) expression in addition to reduced TLF-1 binding and uptake. To determine whether the expressed VSG or expression site associated genes (ESAGs) contribute to TLF-1 resistance we prepared a TLF-1 resistant T. b. brucei with a selectable marker in a silent bloodstream expression site (BES). Drug treatment allowed rapid selection of trypanosomes that activated the tagged BES. These studies show that TLF-1 resistance in T. b. brucei is largely independent of the expressed VSG or ESAGs further supporting the central role of HpHbR expression in TLF-1 susceptibility in these cells.